The female protective effect against autism spectrum disorder - Emilie M. Wigdor; Daniel J. Weiner; Jakob Grove; Jack M. Fu; Wesley K. Thompson; Caitlin E. Carey; Nikolas Baya; Celia van der Merwe; Raymond K. Walters; F. Kyle Satterstrom; Duncan S. Palmer; Anders Rosengren; et al. (Elsevier, 2022)
Summary: Autism spectrum disorder (ASD) is diagnosed three to four times more frequently in males than in females. Genetic studies of rare variants support a female protective effect (FPE) against ASD. However, sex differences in common inherited genetic risk for ASD are less studied, particularly within families. Leveraging the Danish iPSYCH resource, we found siblings of female ASD cases (n = 1,707) had higher rates of ASD than siblings of male ASD cases (n = 6,270; p < 1.0 × 10−10). In the Simons Simplex and SPARK collections, mothers of ASD cases (n = 7,436) carried more polygenic risk for ASD than fathers of ASD cases (n = 5,926; 0.08 polygenic risk score [PRS] SD; p = 7.0 × 10−7). Further, male unaffected siblings under-inherited polygenic risk (n = 1,519; p = 0.03). Using both epidemiologic and genetic approaches, our findings strongly support an FPE against ASD's common inherited influences.